Outdoor Design Strategies to Improve Thermal Comfort in the Area of the Faculty of Engineering, University of Brawijaya Malang - Reza Maulana Mujahiddin; Wasiska Iyati (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
The thermal environment affects a person's heat loss through two factors, namely climate and personal factors. Climate factors include natural land cover, evapotranspiration, geometry effects, anthropogenic, and increased air pollution. This research examines how to reduce the temperature of the microclimate in the outer space of the Faculty of Engineering, Universitas Brawijaya Malang by modifying the surface scopes and vegetation. This study uses descriptive-evaluative research methods and simulations using Autodesk Flow Design software. The results showed that in the morning the air temperature and average wind speed were still at a comfortable interval. During the day the air temperature has begun to rise above the comfortable threshold, plus the irregular wind speed, which is sometimes too low and sometimes too big. Whereas in the afternoon the air temperature returns to enter a comfortable interval, but the wind speed is still in the uncomfortable range. The results of choosing a good surface-scoping material to be applied to the object of research are grass blocks and paving blocks with a mixture of color pigments, as well as giving a white coating to asphalt material. Whereas for vegetation the best tree configuration patterns are linear and grid. The selection of tree species that have a major role in reducing the temperature of the microclimate (shading), namely kiara payung, beringin, ketapang, and tanjung, while trees that play a good role in reducing wind speed are glodogan trees poles and palms.